GOITRE : Monstrous Public Health Problem In Bhandara District - Kulkarni S. W; Rao V. G (Wolters Kluwer Medknow Publications, 1989)
x A field study including clinical survey was carried out in five villages under Primary Health Centre Darekasa in Bhandara District during April to July 1986, to determine the presence and prevalence of goiter. Of the 2245 persons surveyed, enlarged thyroid was observed in 794 individuals â€"35.36% of the population. The prevalence rate in different villages ranged from 29.68% to 54.77%. The highest prevalence rate was found in the age group of 6-10 years (64.88%) followed by the pubescence period of 11-15 years (49.33%). Females over the age of 15 years had a 18.5 times greater prevalence than males. Large goiters (grade III & IV) were relatively more common in females above the age of 30 years, though grade I and II goiters were seen in 6-15 years age group. Goitre was seen in people of all castes and communities but Gonds and Pawars showed a higher prevalence. A familial aggregation was observed.